Basal Cell Carcinoma in Asians: A Retrospective Analysis of Ten Patients - Michael G. Moore; Richard G. Bennett (Journal of Skin Cancer)
Background. Few studies have been done that characterize basal cell carcinoma (BCC) in Asians because this tumor is relatively uncommon in this population group. Objective. To characterize BCC in Asians. Methods. We retrospectively examined fifteen patient variables and eight tumor variables of ten Asian patients with BCC and compared these results to those of thirty matched Caucasian controls with BCC. Results. Asians developed their first BCC at an older age than the age of first BCC in Caucasian controls (68.9 years versus 58.3 years; 𝑃<0.05). During their lifetime, Asians had fewer BCCs than the number of BCCs in Caucasian controls (1.11 versus 5.41; 𝑃<0.02), despite a similar estimated lifetime daily sun exposure (hours/day) for both groups. Compared to BCCs in Caucasian controls, a higher percentage of BCCs in Asians were clinically pigmented (50.0% versus 3.3%; 𝑃<0.01). Conclusion. Asians develop BCCs later in life and develop fewer BCCs over their lifetime than Caucasians, despite similar estimated lifetime daily sun exposure. This finding is probably due to skin pigmentation in Asians being more protective of ultraviolet light than skin pigmentation in Caucasians.